Values of Discipline Character in Class I Student's Book Elementary School Theme is Myself - Muhammad Sobri; Umar (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the content of discipline character values ??contained in the handbook for the first graders This study aims to describe the content of the discipline character values ??contained in the handbook for the first graders of the Tema Diriku Elementary School. This research is included in the content analysis with implementation through six stages, namely: collecting data; determining the sample; recording data; reduction; drawing conclusions, and describing the research results. The 2013 Revised Edition of the 2017 Elementary School Curriculum Textbook published by the Ministry of Education and Culture is this study's data source. The book consists of four sub-themes as the object of research is the content of discipline character values ??contained in the first-grade elementary school student textbook, my theme. The results showed that (1) The Book of Grade I Elementary School Students, Revised Edition 2017 Edition of the Ministry of Education and Culture, contained four sub-themes, namely sub-theme 1: Me And My New Friends, Sub-theme 2: My Body, Sub-theme 3: I Take Care of My Body, and Subtheme 4: I'm Special. Each sub-theme consists of lessons one to six lessons. The total number of pages of this student book is 146 pages. 2) there is a variance in the content of disciplinary character values ??in each sub-theme. The number of sub-theme 1 is 27.8%, sub-theme 2 is 28.6%, sub-theme 3 is 34.1% and sub-theme 4 is 0.0%